PENGARUH KARAKTERISTIK PEKERJAAN DAN DUKUNGAN ATASAN TERHADAP KEPUASAN KERJA DENGAN MEDIASI KOMITMEN ORGANISASIONAL PEGAWAI (STUDI PADA BALAI REHABILITASI SOSIAL KABUPATEN PEMALANG DAN KOTAMADYA TEGAL) - Chasanatin, Chasanatin (Students Journal of Economic and Management, 2012)
This study aims to examine and describe the influence of supervisor support and job characteristics on job satisfaction with the mediation of employee organizational commitment on Social Rehabilitation Center District Municipality Pemalang and Tegal. Research technique used is the census methods. engineering test data used in this study include Test Model Testing, Regression Analysis, Hypothesis Testing and Testing Mediation Effects. The results of the analysis and discussion of this study indicate that the characteristics of the job and employer support has a positive influence on organizational commitment. Job characteristics, supervisor support and organizational commitment have a positive effect on job satisfaction Keywords : job characteristics, supervisor support, organizational commitment and job satisfaction.